Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732759
|View full text |Cite
|
Sign up to set email alerts
|

OutsideMe

Abstract: External self-image is often used as an effective tool to enhance dancing technique, choreography, creativity, and expression. The traditional tools of presenting external image, such as mirrors or videos, are limited in their mobility, perspective, and immediacy. To address the issue, we present OutsideMe, a vision-sync mixed reality system that enables dancers see their body movements as external observers through a headmounted display (HMD) device. This system captures dancer's posture and blends it into sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Meanwhile, we found that the number of trials needed for the participants to capture their virtual body was not particularly high (10)(11)(12)(13)(14), based on the two graph lines associated with the first and second groups for the avoiding timing in Fig. 13 becoming closer or crossing at approximately those points.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Meanwhile, we found that the number of trials needed for the participants to capture their virtual body was not particularly high (10)(11)(12)(13)(14), based on the two graph lines associated with the first and second groups for the avoiding timing in Fig. 13 becoming closer or crossing at approximately those points.…”
Section: Discussionmentioning
confidence: 89%
“…Martin et al investigated replacing body parts with digitized unnatural objects such as whisks and hammers to understand how humans perceive their body and its operations [10]. In addition, out-of-body experiences, which are a sensation of one's consciousness leaving one's body [11], can be linked to BOI and have received wide attention by not only neuroscientists and philosophers but also computer scientists/engineers [12], [13]. Other related studies revealed that people could experience the full body-swapping illusion [14].…”
Section: Body Illusion and Embodimentmentioning
confidence: 99%
See 1 more Smart Citation
“…A large-scale AR mirror for user training is presented where the mirror allows users to see their movements providing them visual feedback [21]. In [22], AR is used to present virtual dancer as an instructor or a dance partner and enables user to see their body movements as an external observer. Clay et al [23] adapted and integrated AR related tools to enhance the emotion involved in cultural performances.…”
Section: Introductionmentioning
confidence: 99%
“…Wearing a head mounted display (HMD) has been becoming a realistic approach than personal training than past few years because of the development of low-cost and high-performance HMDs for commercial use 1 . There are several studies that have used HMDs as means of enhancing a training in the context of for tai-chi with video see-through HMD [1], as well as ballet [3]. These studies have shown their value as early prototypes and explorations in training with HMDs.…”
Section: Introductionmentioning
confidence: 99%